COMPARISON OF EXTRAPERITONEAL AND TRANSPERITONEAL RADICAL CYSTOPROSTATECTOMY IN TERMS OF FIRST 30 DAYS OUTCOMES - Sajjad, Mudassar; Zia, Qamar; Sabir, Haroon; Kiani, Faran; Nawaz, Muhammad; Razzaq, Sohail; Habib, Bilal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the first 30-day outcomes of Trans-peritoneal and Extra-peritoneal Radical cysto-prostatectomy. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, from Mar 2015 to Mar 2019. Methodology: A total of 100 patients who underwent Radical cystoprostatectomy were observed in two groups either by extra or trans-peritoneal approach. Patients diagnosed with carcinoma urinary bladder (both muscle and non-muscle invasive) vetted through multidisciplinary meeting, with or without neo-adjuvant chemotherapy were included. Patients undergoing salvage cystectomy or any previous open abdomino-pelvic surgery were excluded. The standard techniques were used for both approaches. Variables under study were recorded for first 30-day-followup period. Results: The mean age was 59.9 ± 7.231 years (range=34-80). In extra-peritoneal group the mean duration of surgery was 5.6 ± 1.16 hours comparing to 7.2 ± 1.34 hours in the trans-peritoneal group. Statistically significant trend was also noted in the favour of extra-peritoneal group for stay in Intensive care in post-operative period (3.00 ± 1.19 days/4.77 ± 1.20, p<0.001) as well total stay in the hospital (6.06 ± 2.8 days/ 11.74 ± 4.17, p<0.001). Overall comparison of total number of complications as per Clavien-Dindo system in both groups was insignificant (p=0.136), however a significant trend in favour of extraperitoneal group was noted with respect to major wound dehiscence as well rate of blood transfusion (p<0.001). Conclusion: Extra-peritoneal approach showed a favourable trend in terms of operative time and early recovery after radical cysto-prostatectomy.